2011
DOI: 10.1590/s0100-06832011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Root growth of tomato seedlings intensified by humic substances from peat bogs

Abstract: Peats are an important reserve of humified carbon in terrestrial ecosystems. The interest in the use of humic substances as plant growth promoters is continuously increasing. The objective of this study was to evaluate the bioactivity of alkaline soluble humic substances (HS), humic (HA) and fulvic acids (FA) isolated from peats with different decomposition stages of organic matter (sapric, fibric and hemic) in the Serra do Espinhaço Meridional, state of Minas Gerais. Dose-response curves were established for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…According to Canellas et al (2008), humic substances have auxinic action. This is in agreement with Silva et al (2011), who reported, as the main physiological effect, the increase in root development, according to the species, plant age, source and concentration. According to Casimiro et al (2001), this phytohormone activates the division of pericycle cells, acting on the initial stages of formation of the root primordium, directly influencing root development, which may have affected the mean increments in collar diameter and plant height observed in the present study.…”
Section: Resultssupporting
confidence: 93%
“…According to Canellas et al (2008), humic substances have auxinic action. This is in agreement with Silva et al (2011), who reported, as the main physiological effect, the increase in root development, according to the species, plant age, source and concentration. According to Casimiro et al (2001), this phytohormone activates the division of pericycle cells, acting on the initial stages of formation of the root primordium, directly influencing root development, which may have affected the mean increments in collar diameter and plant height observed in the present study.…”
Section: Resultssupporting
confidence: 93%
“…Pesquisadores têm utilizado cultivares miniatura, porém de frutos redondos, denominada Mini-Tom (MT), como modelo genético para estudos básicos, genéticos e fisiológi-cos (WANG et al, 2005;WATANABE et al, 2007;SILVA et al, 2011;MONTEIRO et al, 2012;PÉ-REZ;AHMED, CABEZAS, 2013). No entanto, pouco se sabe a respeito do tipo de herança condicionado pelas plantas anãs ao cruzar com plantas de hábito de crescimento indeterminado.…”
Section: Introductionunclassified
“…BALDOTTO et al (2009;2012;2013) found that humic acid applications close to 20mmol L -1 C to gladiolus bulbs, pineapple seedlings and croton cuttings concentrations increased the biomass. The positive effects on the accumulation of shoot matter in humic acid treated sunflower plants can be explained by different physiological factors such as increased synthesis of chlorophyll (BALDOTTO et al, 2009), increased nutrient uptake (NARDI et al, 2002), growth promotion of the root system (BALDOTTO et al, 2011) and the formation of root hairs (SILVA et al, 2011).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%